Knight Rider lamp / Mohd Shahrul Mohd Sallah and Muhafes Mohamad - Mohd Sallah, Mohd Shahrul; Mohamad, Muhafes (1999)
The star of the famous TV series Knight Rider used a super computerized car which had a front display of five light flashing one hv one from left to right and then from right to left It also had sound effect of live tones that came one hv one with the flashing of the lights Several circuits are available for the Hashing action, but none of them (even the commercial ones) produces the sound effect T he circuit described here can do that too square wave is generated from l('l . a 555 timer, which is fed to pin 14 of counter 1C 2 1C2 is an 1C4017 counter which accepts square wave and give ten mutually independent outputs T he outputs, using rectifiers, produces the effect of bulbs flashing from left to right and then right to lenThese outputs are fed to pm .1 of another timer 1C which gives the sound effect